Collegiate management in inpatient pediatric unit from health professionals’ perspective: Health Services Administration; Health Manpower; Hospital administration. - Menezes Brito, Maria José; Cozer Montenegro, Lívia; Peixoto, Tereza Cristina; da Silva Caram, Carolina; Rezende, Lilian Cristina (O Mundo da Saúde, 2019)
The hospitals make up the tertiary level of Health Care Network, which include sets of procedures in the context of the Health System, it involves high technology and high cost and integrates other health care levels. Thus, the establishment of a network of services implies a new management model whose assumptions are focused on the quality of care at different levels of health care. One of management models that favor decentralization and participation of professionals is a model of collegiate management. Thus, the objective of the study was to know the collegiate management from the perspective of professionals in a pediatric unit of a university hospital. For this, a qualitative research, analytical and descriptive was conducted with 16 professionals from different categories of of a university hospital. The data collection took place through interviews with semi structured script, which were submitted to content analysis. It was noticed that professionals consider that the collegiate management has barriers they are lack of communication between professionals and between them and the directors; infrequent meetings; lack of transfer and sharing of information and the participation of the directors and difficulty of performing the teamwork. In contrast, the teamwork is effective in multidisciplinary projects. We conclude that the collegiate management happens in a corporatist and undemocratic means, demonstrating the need for transformation of the organizational culture for it to be participatory.